Development and validation of the Transgender Adolescent Stress Survey-Dysphoria - Schrager, Sheree M.; Goldbach, Jeremy T.; Wood, Jules K.; O'Brien, Rory P.; Dunlap, Shannon L.; Rhoades, Harmony (Frontiers in Psychology, 2024)
Objective Transgender and nonbinary adolescents (TNBA) may experience gender dysphoria arising from incongruities between their body and their gender. Prior dysphoria measures have largely focused on clinical diagnosis with little regard to comparability of forms for people assigned male or female at birth, overall psychometric performance, or applicability to nonbinary populations. This study develops and validates the Transgender Adolescent Stress Survey-Dysphoria (TASS-D), intended to address these gaps. Methods The current study recruited a U.S. national sample of TNBA (N = 444, aged 12–17; 65.5% White, 9.5% Black, 9.5% Latine, 15.5% other ethnicity; 34.7% transmasculine, 17.3% transfeminine, 38.3% nonbinary, 9.5% agender). The item pool was developed from life history calendars, a modified Delphi process, and cognitive interviews with TNBA. Scale development included factor analysis, item response theory modeling, measurement invariance testing, and reliability analyses. Associations were examined between the TASS-D and existing measures of gender dysphoria (convergent validity), gender minority stress (divergent validity), and behavioral health outcomes (criterion validity). Results TASS-D and its subscales (body distress and gender expression burden) were significantly and strongly associated with gender dysphoria; significantly but weakly associated with gender minority stress; and significantly associated with most indicators of psychological distress including depressive, anxiety, and posttraumatic stress symptoms, suicidal behaviors and nonsuicidal self-injury. Conclusions The TASS-D is a reliable and valid measure of gender dysphoria for TNBA, offering notable benefits over existing measures: It is psychometrically sound, inclusive of all gender identities, and does not assume that respondents identify binarily or desire medical transition as a terminal goal.